The televised goodbye to D10s: from the Casa Rosada to our homes - Ezequiel Ramon Pinat (Funes)
A few hours after the announcement of his death, Argentina started a long goodbye to the ‘Pibe de Oro’ (Golden Boy), covered in resignation and sadness. A farewell was organised at the Casa Rosada (presidential house), where citizens could go to bid their last farewell despite Covid restrictions. This article aims to analyse its live TV coverage by the Telenoche program, applying ‘media events’ theory. Such a focus was developed by Dayan and Katz in the communication field and analyses events broadcast as a narrative genre. Organised outside the media, events are planned, previously announced and broadcasted live as an interruption of daily life, against routine TV shows, which have been broadly studied in the academy.